Exchange Rate Policy and the Management of Official and Private Capital Flows in Africa - Pattillo, Catherine (IMF Working Papers; Working Paper ;, 2004)
We focus on the management of highly persistent shocks to aid flows, including PRSP-related increases in net inflows, in three 'post-stabilization.' African economies with de jure flexible exchange rates. Such shocks have beneficent long-run effects, but when currency substitution is high they can produce dramatic macroeconomic management problems in the short run. What is the appropriate mix of money and exchange rate targeting in such cases, and what is the role of temporary sterilization? We analyze these issues in an intertemporal optimizing model that allows a portion of aid to be devoted to reducing the government's seigniorage requirement. This creates a strong link between official aid flows and private capital flows. When the credibility of policymakers' commitment to low inflation is firm, some degree of dirty floating, with little or no sterilization of increases in the monetary base, is the most attractive approach in the short run.